Erosion Resistance Behavior of SS304 Steel Hardfaced By SMAW With Addition of Molybdenum - Jindal, Chamkaur; Sidhu, Hazoor Singh (Asian Review of Mechanical Engineering, 2013)
In this work the degradation of the steel SS304 used in pulverized coal burner nozzle is studied under the solid particle erosion conditions. Steel is hardfaced by tubular hardfacing electrodes of high chromium type and further Molybdenum content is added in the hardfacing electrode powder. The hardfacing is done by shielded metal arc welding process. Erosion test is conducted using Air Jet Erosion Testing Rig by varying the working temperatures (room temperature and 400°C) and impact angle of 30° and 90°. It is observed that by increasing the molybdenum content the degradation by erosion reduced at 90° impact angle at both room temperature and 400°C temperature. Microstructure characterization and microhardness analysis is also done along with SEM/EDS analysis. The elements in the hardfacing layer are uniformly distributed as observed by the EDS analysis and the content of tungsten and molybdenum increased in hardfacing layer than the substrate material. The increase in percentage of Molybdenum and tungsten improves the formation of carbides in hardfacing layer. Normally the harder materials have high erosion resistance at 30° impact angle but in our case the erosion resistance is maximum at 90° impact angle. The microstructure shows dendritic formation.